Implementasi CMS Untuk Company Profile Studi Case Pusat Inovasi Primakara - Wayan Sutrisna; I Putu Satwika (Primakara University, 2019)
As time goes by the development of technology is growing. Many benefits can be drawn from technological developments, one of which is business development. The STMIK Primakara campus has a division called the Innovation Center providing innovations to startup activists or encouraging startups to be able to develop further in the future by providing innovation and collaborating with business incubators at STMIK Primakara. However, information media or company profiles are still not well-developed, making it difficult in the future to provide innovative content to startup activists. Knowing this, the authors are interested in creating a company profile website by implementing a Content Management System (CMS). The result of this research is a website that is able to deliver innovative content so that website visitors will get appropriate information and can also encourage the creation of startups that can grow big in the future.